Towards visualization of symptomatic carotid stenosis - Gass, Achim; Meairs, Stephen; Neff, Wolfgang; Hennerici, Michael G. (Archives of neurology, 2001)
A 62-YEAR-OLD woman was admitted for suspected recent onset of sensory transient ischemic attacks (8 episodes lasting 10-30 seconds each with numbness and tingling in the left hand and forearm). Her neurological history was unremarkable. She had no abnormal findings on neurological examination. Holter electrocardiography results were normal and transesophageal echocardiographyfindings failed to reveal a thromboembolic source. Results of magnetic resonance imaging and ultrasound studies demonstrated a hemodynamically relevant proximal right internal carotid artery stenosis (Figure 1 and Figure 2), and she underwent right carotid endarterectomy. Postoperatively and at 4-month follow-up no further neurological symptoms occurred, and results of Doppler studies showed no signs of obstruction.
Gesehen am 31.03.2021